Emma Watson The Watsons completed - Aiken, Joan; Austen, Jane 1775-1817. (Boston : Compass Press, 1997)
An ingenious continuation of one of Jane Austen's intriguing unfinished novels,The Watsons. Emma Watson returns home after 14 years spent with a beloved aunt, whose re-marriage has caused a significant change in Emma's circumstances. Used to a life of ease, warmth and intelligence, Emma is thrust back into a home where, with one exception, her sisters are petty and jealous, if not vulgar, her father is ill and weak, and her brothers are not men of fine minds. This is a poignant exploration of a young lady's endurance in the face of reduced circumstances, and in true Jane Austen fashion, there is an admirable hero to make all right in the end.
Completion of The Watsons, an unfinished novel by J. Austen.
81140
Keywords: Large type books; England -- Social life and customs -- 18th century -- Fiction; Domestic fiction; Historical fiction